Elementary Students’ Online Information Problem Solving (IPS) in a Science Classroom - Jin, Qingna; Kim, Mijung; Wong, Suzanna (Alberta Journal of Educational Research, 2023)
Supporting students to become critical consumers of online information is one of the most urgent agendas in education today. In schools around the world, students are engaging in online information problem solving (IPS) tasks to develop critical thinking and problem-solving skills by searching and evaluating online information. This qualitative case study explored how 5th and 6th Grade students experienced online IPS using their metastrategic knowledge—that is, knowing why and how to use certain strategies in specific instances. Data collection methods included classroom observation, classroom video recording, fieldnotes, the think-aloud strategy, interviews, and students’ reflections about their writing and artifacts. The study’s findings indicated that students actively engaged their metastrategic knowledge during the online IPS processes to understand and examine the validity of information and sources and to effectively communicate their IPS results to others. In the process, students also developed ownership and responsibilities for problem solving with reliable information. Based on the study’s findings, this article summarizes the process and discusses the pedagogical implications of elementary students’ online IPS. Keywords: information problem solving; metastrategic knowledge; information evaluation; elementary science; qualitative research Aider les élèves à devenir des consommateurs critiques d'information en ligne est actuellement l'un des objectifs les plus urgents en éducation. Dans les écoles du monde entier, les élèves s'engagent dans des tâches de résolution de problèmes d'information en ligne pour développer leur esprit critique et leurs compétences en résolution de problèmes en recherchant et en évaluant des informations en ligne. Cette étude de cas qualitative s’est penchée sur l'expérience d'élèves de 5e et 6e années en matière de résolution de problèmes d'information en ligne alors qu’ils utilisaient leurs connaissances métastratégiques, c'est-à-dire qu’ils déterminaient pourquoi et comment utiliser certaines stratégies dans des cas spécifiques. Les méthodes de collecte de données comprenaient l'observation de la classe, l'enregistrement vidéo de la classe, les notes de terrain, la stratégie de réflexion à voix haute, les entretiens, ainsi que les réflexions des élèves sur leurs écrits et leurs artefacts. Les résultats de l'étude indiquent que les élèves ont activement utilisé leurs connaissances métastratégiques au cours des processus de résolution de problèmes d'information en ligne afin de comprendre et d'examiner la validité des informations et des sources ainsi que de communiquer efficacement ces conclusions aux autres. Au cours de ce processus, les élèves ont également développé l'appropriation et la responsabilité de la résolution de problèmes à l'aide d'informations fiables. Sur la base des résultats de l'étude, cet article résume le processus et discute des implications pédagogiques de résolution de problèmes d'information en ligne des élèves du primaire. Mots clés : résolution de problèmes d'information ; connaissances métastratégiques ; évaluation de l'information ; sciences élémentaires ; recherche qualitative